Propuesta de implantación de un Sistema de Calidad e Inocuidad en la Línea de Pasta de Frutas de la Unidad Empresarial de Base “La Conchita” (Análisis de Peligros y Puntos Críticos de Control). - Guisha Llamba, Edison Tomas (2012)
The following investigative work was carried out in the Line of Pasta of Fruits of the Managerial Unit of Base The Shell and it embraced the study of the subsystem referred to the Administration of the Quality. He took as general objective of the investigation: To elaborate a proposal for the installation of the System of Quality and Innocuousness in the Line of Pasta of Fruits. They were also traced the following specific objectives: to analyze the Cuban regulatory scheme NC 136:2007, NC 147:2005 and the effective resolutions in the field of the Quality and Innocuousness in the Line, to diagnose the current conditions of the Main Dangers and Critical Points of Control in the Line of Pasta of Fruits and to propose solutions to minimize the discovered risks and the detected problems. You arrived to the following summations: The systematic application of the NC 136: 2007 and the NC 147: 2005 allow identifying the dangers and the measures to minimize them that which guarantees the quality and innocuousness of the products of the line of Pasta of Fruits. The main problems that affect the quality of the endproduct are: no fulfillment of the time of cooking, the non uniformity of the mass, contamination of the product for toxic gases and accumulation of the gases that are emanated of the boilers. They were identified as Critical Points of Control in the Line of Pasta of Fruits the one reviewed of fresh fruit and of semimanufactured pulp. The application of the action plan proposed to the detected problems and of the Manual of Quality and Innocuousness for the Line of Pasta of Fruits will allow minimizing the risks to perfect the System of Quality and Innocuousness APPCC (Analysis of Dangers and Critical Points of Control) of the company.